Kant’s philosophical modesty. Towards a typology of philosophical theology - Andrey Sudakov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
Kant’s doctrine of religion has been repeatedly accused from different perspectives of having committed a rationalistic reduction of religious faith to a «faith of reason», or of claims to reinterpret by means of reason the body of beliefs of a revealed religion. The article investigates the Königsberg philosopher’s ideas concerning the boundary strip between philosophical and biblical theology as well as the criterion of an illegal trespass of this borderline. Only the philosopher’s claim to complement, modify or reinterpret of the dogmatic tenets of a historical religion, by means of reason alone, or to review the practical targeting of the dogmatic doctrines of a church, i.e. an «engagement in theology», proves to be, according to Kant, such a criterion; by contrast, an interpretation of church dogmatics which is devoid of any creedal claims does not imply an illegitimate reinterpretation of dogmatics. Contrarily, a criticism of Kant for such a reinterpretation, or even a mere presumption of its possibility in principle, does itself imply, as a matter of fact, a trespass of borderlines as determinated by Kant, a kind of hermeneutical dumbness of such criticism, its incapacity to accept its opponent in its specific intellectual quality. Such a dumbness may be caused by the difference in conceptions about the possibility and the essence of rational philosophical theology in doctrines of religion developed from an irrationalist, a speculative metaphysical and a moral-practical perspective, the first of which was intrinsically foreign to Kant’s mind, the second had been overcome by him in the result of the Copernican turn, and only the third made up the core of his own critical philosophy of religion. On this third position of philosophical theology comprehensive cognition of «God’s own properties» is held to be unattainable for human beings, and yet is everything knowable in the field of faith and theology acknowledged to be a product of practical reason. The limitation upon the claims of «theory» provides such a philosophical theology with genuine philosophical modesty, while its affirmation of ethico-theology as the only possible basis of rational doctrine of religion allows it to display a genuine awareness of the philosophy’s dignity as a science of reason. F.K.Forberg’s and Leo Tolstoy’s philosophies of religion, in spite of their superficial resemblance with the ethico-theological project, do not distinguish themselves at the least with that kind of philosophical modesty, digressing in two different ways from the science of reason towards a tcommon sense theory and providing an opportunity for critique of established religion from the perspective of the latter.